Public Deliberation and Talking Shops: Some Critical Thoughts - San José Alonso, Elena (Razón y fe, 2020)
Talking shops have played a major role in social and democratic life of societies and, from that position, they have always faithfully portrayed the essence of every political period: the underlying issues, the forces in dispute, the longing for progress. This kind of informal but institutionalized conversation has survived changes over time and successfully adapted to the structural transformations of society. However, that adjustment has been accompanied by some important changes in the very nature of these gatherings —now usually talk shows— that are not very constructive. Throughout this article, we will address some of these elements and we will explore their relationship with the kind of citizenship they contribute to build.